Variability Studies in some Perilla (P. frutescens L. Britton) Accessions of North-east India - Hussain, Safiqul; Changkija, S.; Hore, D. K. (International Journal of Bio-resource and Stress Management, 2023)
Fifty Perilla frutescens (L.) Britton accessions, collected from different parts of northeastern region of India including one exotic collection from Australia were evaluated to assess the genetic variability, heritability and genetic advance for thirteen morphological and yield traits. Significant genetic variation was observed for all the characters. Higher estimates of heritability coupled with high to moderate estimates of genetic advance as percentage of mean were observed for plant heights, number of leaves plant-1, petiole length, number of primary branches plant-1, length of main inflorescence, number of inflorescences plant-1 and leaf breadth, seed yield plant-1, 1000-seed weight, showing the possibility of improvement of these traits through selection.